N,N `-Bis[(E)-(2-chloro-8-methylquinolin-3-yl)methylidene]ethane-1,2-diami ne - Prasath, R.; Bhavana, P.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The complete molecule of the title compound, C24H20Cl2N4, is generated by a crystallographic inversion centre. A kink in the molecule is evident [C-N-C-C torsion angle = -147.0 (3)degrees] owing to the twist in the central ethylene bridge. Further, there is a small twist between the imine [N=C = 1.267 (3) angstrom] and quinoline residues [N-C-C-C = -12.4 (4)degrees]. In the crystal, a combination of pi-pi [pyridine-benzene centroid-centroid distance = 3.5670 (14) angstrom] and C-H center dot center dot center dot N contacts leads to supramolecular chains propagating in [010].